Egg Protein Transferrin-Derived Peptides IRW and IQW Regulate Citrobacter rodentium-Induced, Inflammation-Related Microbial and Metabolomic Profiles - Ma, Yong; Ding, Sujuan; Liu, Gang; Fang, Jun; Yan, Wenxin; Duraipandiyan, Veeramuthu; Al-Dhabi, Naif Abdullah; Esmail, Galal Ali; Jiang, Hongmei (Frontiers in Microbiology, 2019)
Bioactive peptides that target the gastrointestinal tract can strongly affect the health of animals and humans. This study aimed to evaluate the abilities of two peptides derived from egg albumin transferrin, IRW and IQW, to treat enteritis in a mouse model of Citrobacter rodentium-induced colitis by evaluating serum metabolomics and gut microbes. Forty-eight mice were randomly assigned to six groups: basal diet (CTRL), intragastric administration Citrobacter rodentium (CR), basal diet with 0.03%IRW (IRW), CR with 0.03% IRW (IRW+CR), basal diet with 0.03%IQW (IQW) and CR with 0.03% IQW (IQW+CR). CR administration began on day 10 and continued for 7 days. After 14 days of IRW and IQW treatment, serum was collected and subjected to a metabolomics analysis. The length and weight of each colon were measured, and the colon contents were collected for 16srRNA sequencing. The colons were significantly longer in the CR group, compared to the CTRL group. A serum metabolomics analysis revealed no significant difference in microbial diversity between the six groups. Compared with the CTRL group, the proportions of Firmicutes and Actinobacteria species decreased significantly and the proportions of Bacteroidetes and Proteobacteria species increased in the CR group. There were no significant differences between the CTRL and other groups. The serum metabolomics analysis revealed that Infected by CR increased the levels of oxalic acid, homogentisic acid and prostaglandin but decreased the levels of L-glutamine, L-acetyl carnitine, 1-methylhistidine and gentisic acid. Therefore, treatment with IRW and IQW was shown to regulate the intestinal microorganisms associated with colonic inflammation and serum metabolite levels, thus improving intestinal health.